Prisoner reentry and reintegration : perspectives of the women involved in Outcare's St John of God Women's Program - Lackner, Melissa (2012)
Promoting and supporting the successful transition of prisoners into the wider community following release is a challenge that has received increasing attention on the part of both researchers and policymakers alike, especially considering the great costs to the community of crime and incarceration. Consequently, literature in this area has grown considerably, spurred by criminal justice interests in reducing recidivism and social justice interests in improving the opportunities and life circumstances of returning prisoners. This literature has however, traditionally been comprised of international studies based exclusively on male populations or with disregard for the differentiation between males and females. Although there is now a slowly growing body of female-specific literature, fuelled by the increasing imprisonment rates among women, more remains to be learnt about the specific experiences and needs of female prisoners, especially from an Australian perspective. Recognising the need to address the paucity of Australian-based female-specific knowledge, this study explores the release concerns and service needs of female prisoners returning to the Perth metropolitan community. Drawing upon the narratives of eleven women who sought post-release support from Outcare's St John of God Women's Program, this research highlights two outstanding and interrelated themes. Firstly, following release there is a distinct need for women to develop a personal sense of stability within the community, including in particular, the establishment of safe, affordable and appropriate housing, financial security, the maintenance of sobriety, relational connection or reconnection, and immersion into prosocial pursuits. Secondly, in achieving such stability and, more importantly, maintaining it, there is a clear need for support for women, both in personal and non-personal terms. Ultimately, this research points to the critical role of comprehensive and female-focussed throughcare programs and services that can address critical short-term release needs, and provide opportunities for long-term self-sufficiency and sustainability. Furthermore, such services need to be encouraged as a crucial component of the criminal justice system, to ensure that women do not 'slip through the cracks'